Effectiveness of Youth Reproductive Health Program (KRR) on Increasing Knowledge of Reproductive Health - Ika Wuryani; Abela Mayunita (Global Health Science Group, 2023)
Globally WHO reports more than 1.5 million adolescents and young adults aged 10–24 die nearly 5,000 every day. Half of all causes of death caused by physical and mental health disorders are reported to occur since they were 14 years old. Comprehensive sexual education (CSE) plays a central role in preparing young people for a safe life. The purpose of this study is to provide a reproductive health education program to increase knowledge about good and correct reproductive health for SMAIT Al Hidayah Mancak students. This study is a type of intervention research with experimental quasy design. The location used for this research is at Al-Hidayah IT High School in Winong village, Mancak District, Serang Regency-Banten 2023. This study was conducted in March or April 2023. The research sample was 80 students. The bivariate analysis used in this study was the Chi-Square test. Based on the chi square test obtained results (OR 3.32; 95%CI: 1.19 – 9.24; p value: 0.029) There was a statistically significant difference in students' knowledge before and after counseling. The odds ratio (OR) value is 3.32 this result can be interpreted that the provision of health counseling can increase students' knowledge about adolescent reproductive health up to 3 times.